2006
DOI: 10.1159/000090817
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the vertebrate DNMT3 gene family: a possible link between existence of <i>DNMT3L</i> and genomic imprinting

Abstract: DNA methylation plays an essential role in genomic imprinting observed in eutherian mammals and marsupials. In mouse, one of the two de novo DNA methyltransferases, Dnmt3a, and a related protein, Dnmt3L have been shown to be essential for imprint establishment in the parental germline. To gain insights into the evolution of imprinting mechanisms, we have identified and characterized the DNMT3 family genes in other vertebrate species. We cloned cDNAs for chicken DNMT3A and DNMT3B, whose putative protein product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 26 publications
1
48
0
1
Order By: Relevance
“…Although catalytically inactive, biochemical assays have revealed that Dnmt3L facilitates de novo methylation by stabilizing the active conformation of Dnmt3A, this therefore allows a more efficient transfer of methyl groups onto target sequences (Chedin et al, 2002;Jia et al, 2007). It should be noted that Dnmt3L is not only functionally but also evolutionarily linked to the protection of the germline against TEs: Dnmt3L specifically emerged in eutherian mammals, some 150 million years ago, coinciding with an important TE expansion in mammalian genomes (Yokomine et al, 2006;Warren et al, 2008).…”
Section: Host Responses To Tes or How To Live With A Herd Of Squattersmentioning
confidence: 99%
“…Although catalytically inactive, biochemical assays have revealed that Dnmt3L facilitates de novo methylation by stabilizing the active conformation of Dnmt3A, this therefore allows a more efficient transfer of methyl groups onto target sequences (Chedin et al, 2002;Jia et al, 2007). It should be noted that Dnmt3L is not only functionally but also evolutionarily linked to the protection of the germline against TEs: Dnmt3L specifically emerged in eutherian mammals, some 150 million years ago, coinciding with an important TE expansion in mammalian genomes (Yokomine et al, 2006;Warren et al, 2008).…”
Section: Host Responses To Tes or How To Live With A Herd Of Squattersmentioning
confidence: 99%
“…Whereas Dnmt3a and Dnmt3b orthologs are found widely among distant eukaryotic species, a third Dnmt3 member, Dnmt3-like (Dnmt3l), has evolved uniquely in mammals (Yokomine et al, 2006). This gene encodes a catalytically inert protein that is unable to methylate DNA substrates alone but serves as a regulator of the de novo methylation machinery.…”
Section: Introductionmentioning
confidence: 99%
“…The chicken genome contains homologues of each mammalian DNMT (Table 1) with the exception of DNMT3L (Yokomine et al, 2006) each having high conservation with mammalian proteins; with DNMT1 having 94% identical amino acid sequence (Tajima et al, 1995).…”
Section: Chicken -Gallus Gallusmentioning
confidence: 99%